Clinicopathological features and outcomes of parenchymal rejection in liver transplant biopsies. Issue 6 (16th April 2020) - Fels Elliott, Daffolyn Rachael; Tavakol, Mehdi; Lucas, Calixto‐Hope; Sheahon, Kathleen; Kakar, Sanjay; Hameed, Bilal; Ferrell, Linda D; Gill, Ryan M
Abstract : Aims: The aim of this study was to perform a comprehensive retrospective analysis of liver transplant biopsies with parenchymal rejection (PR) at our institution, including histological features, laboratory values and follow‐up biopsies, and to compare PR with portal‐based acute cellular rejection (ACR). Methods and results: Biopsies from 173 patients were evaluated (retrospective database search 1990–2017), including 49 isolated PR, 35 PR with portal ACR (PR/ACR), 34 mild ACR and 52 moderate ACR cases. The rise and fall of serum liver enzymes was calculated as a measure of acute liver injury and response to immunotherapy, respectively. Isolated PR was associated with delayed‐onset acute rejection ( P < 0.001), as well as younger age ( P = 0.004), and showed a similar rise in liver enzymes to mild ACR. PR/ACR and moderate ACR showed the highest elevations in transaminases ( P < 0.05). Isolated PR on an initial biopsy was associated with recurrent episodes of PR ( P = 0.01), chronic ductopaenic rejection ( P = 0.002) and chronic vascular rejection ( P = 0.017). Immunohistochemistry for C4d was performed, and strong C4d staining of venules was only detected in one severe isolated PR case (one of three, 33%) and one moderate ACR case (one of 20, 5%). Conclusions: Isolated PR represents a form of late acute rejection with distinct clinical and histological features. There is value in reporting PR in liver transplant biopsies to identify patients at higher risk of developing recurrent PR and chronic rejection. Standardisation of terminology and histological criteria of PR can help in uniform reporting and ensure appropriate management.